UK Biobank's cardiovascular magnetic resonance protocol. Issue 1 (December 2015) - Petersen, Steffen; Matthews, Paul; Francis, Jane; Robson, Matthew; Zemrak, Filip; Boubertakh, Redha; Young, Alistair; Hudson, Sarah; Weale, Peter; Garratt, Steve; Collins, Rory; Piechnik, Stefan; et al.
Abstract Background UK Biobank's ambitious aim is to perform cardiovascular magnetic resonance (CMR) in 100, 000 people previously recruited into this prospective cohort study of half a million 40-69 year-olds. Methods/design We describe the CMR protocol applied in UK Biobank's pilot phase, which will be extended into the main phase with three centres using the same equipment and protocols. The CMR protocol includes white blood CMR (sagittal anatomy, coronary and transverse anatomy), cine CMR (long axis cines, short axis cines of the ventricles, coronal LVOT cine), strain CMR (tagging), flow CMR (aortic valve flow) and parametric CMR (native T1 map). Discussion This report will serve as a reference to researchers intending to use the UK Biobank resource or to replicate the UK Biobank cardiovascular magnetic resonance protocol in different settings.